Bioavailability studies and anticancer properties of malvidin based anthocyanins, pyranoanthocyanins and non-oxonium derivatives. Issue 5 (11th May 2016) - Oliveira, Hélder; Wu, Nao; Zhang, Qian; Wang, Jingyi; Oliveira, Joana; de Freitas, Victor; Mateus, Nuno; He, Jingren; Fernandes, Iva
Abstract : In this study, the gastric transport efficiency of malvidin-3-glucoside and several derivatives was assayed on the MKN-28 cell model. Abstract : In this study, the gastric transport efficiency of malvidin-3-glucoside and several derivatives was assayed on the MKN-28 cell model. The transport efficiency was found to increase for all compounds with the incubation time. Pyranoanthocyanins may slightly impair transport efficiency levels in comparison with native anthocyanins. Among the pyranoanthocyanin derivatives the presence of the carbonyl group and the absence of charge were important for the transport efficiency percentage of oxovitisin and apparently compensated the negative effect associated with the additional ring. Moreover, the antiproliferative properties of these compounds in the MCF-7 cancer cell line were assayed, oxovitisin being the most effective compound in inhibiting the proliferation of MCF-7 cells. Also, a kinetic incorporation of oxovitisin was assayed revealing that this pyranoanthocyanin is quickly incorporated into cells. This study confirms the importance of the natural micro-oxidative processes that occur during the ageing of anthocyanin-containing food and their impact on their bioavailability and bioactivity properties.